Implementation of Serviam Character Education at Saint Theresia Senior High School Jakarta - Noegroho, Albertus (International Journal of Educational Management and Innovation, 2024)
Character education is an important part of shaping students' character in facing the challenges of the times.  Saint Theresia Senior High School implements character education that aligns with the school's vision. How is the implementation of the Serviam value in that school?  There has been no research on this matter yet.  This research aims to explore the implementation of the Serviam value at Saint Theresia Senior High School.  The method used is qualitative.  Data were obtained using interview techniques, observation, and documentation studies.   The results show that the implementation of value education is carried out through (1) learning activities and planning (95% of teachers have prepared lesson plans with Serviam character), implementation in learning (88% of teachers have implemented lesson plans with Serviam character in learning), and in attitude assessment (100% of teachers have conducted attitude assessments with Serviam character).  (2) the development of habitual school culture; (3) extracurricular activities; and (4) daily activities at home and in the community) This research contributes to enriching the literature on character education and provides important input for stakeholders on the development of integrative and systematic character education, thereby serving as input and development in the school curriculum.